(untitled) (Research, Society and Development, 2021)
The struggle of women for the conquest of rights marks the history of societies, through social and political movements, they currently enjoy some rights in the city or in the countryside. Female empowerment is a process of struggles and achievements. Women persisted in transformative political and social movements, such as social inclusion, education, professionalization and for their rights as citizens, constituting the aforementioned empowerment; therefore, it is opportune to associate it with the feminist conception. The dissertation The Trajectory of Peasant Women in Agrovila Paulo Freire in the Municipality of Mossoró-RN aims to analyze the trajectory of women in Agrovila Paulo Freire, Municipality of Mossoró-RN with the aim of fostering female peasant empowerment in the bonds of work, resulting in a filmographic documentary that serves as a pedagogical and identity tool. However, each brings in their life stories their beliefs, utopias and aspirations. Therefore, the research proposes to answer the following research question: How have rural women’s life stories influenced labor relations and economic and social development in Agrovila Paulo Freire? The research is qualitative and descriptive and consists of a documentary that rescues the life story of the participating women and the settlement. In the film, their stories are recreated so that others can watch and understand their individualities, values, cultures and everyday struggles. The documentary can be used as a didactic material in teacher training, in schools or other institutions, showing the viewer a way of ’reading’ history, understanding and understanding reality in a non-dichotomous, not black and white, but also presence of gray tones. In the results and discussions we found the link between formal and non-formal knowledge.